Master of modernity (Оn the example of the poet Kodec) (Herald of Journalism, 2016)
In this publication, the author tells the story of a man was evil Red Empire and forced to move abroad, known Kazakh poet Maralbay Bayshyganuly Kodec, which refers to the creation of not only poetry, but alsojournalistic writings. Also says that the Kazakhs oratory was an element not only art, but also a means of sharing information. Kodec in his creation wrote about the politics and power, social processes in society.
Keywords: publicism; oratory; Kodec poet